Case 3767: Papilio phoebus Fabricius, 1793 (currently Parnassius phoebus; Insecta, Lepidoptera): proposed conservation of prevailing usage of the specific name and that of Doritis ariadne Lederer, 1853 (currently Parnassius ariadne) by the designation of a neotype - Lukhtanov, Vladimir A; Pelham, Jonathan P; Cotton, Adam M; Calhoun, John V (Bulletin of Zoological Nomenclature, 2019)
The purpose of this application under Article 75.6 of the Code is to conserve the specific names of the European ‘Small Apollo’ butterfly Parnassius phoebus (Fabricius, 1793) and the Altai ‘Apollo’ butterfly Parnassius ariadne (Lederer, 1853) in their current usage. Hanus & Theye (2010) discovered that the traditional concept of the name P. phoebus was a misidentification and published actions contrary to Art. 75.6. We herein request that the International Commission on Zoological Nomenclature use its plenary power to set aside all previous type fixations for the nominal species Papilio phoebus Fabricius, 1793, and to designate a neotype representative of the current usage of P. phoebus.
Keywords: Nomenclature; taxonomy; PAPILIONIDAE; PARNASSIINAE; Parnassius; P. phoebus; P. ariadne; P. corybas; European 'Small Apollo' butterfly; Holarctic; Altai 'Apollo'butterfly